Spanish as a foreign language textbooks and Multimodality: a contextualized approach - Efron, Andrés Julio (Universidad Nacional del Litoral, 2021)
The market for Spanish as a foreign language (ELE) has expanded exponentially due to its demographic distribution and the emerging Latin American economies. This produced a great diversity of editorial proposals for manuals aimed at teaching Spanish. This work will explore the multimodal configuration of seven (contextualized) manuals that were published for teaching Spanish in Argentina. Covers and interior design will be analyzed from a perspective that seeks to explain how meaning is constructed from the different available semiotic resources as well as from the semantic expansions that take place as the different options are combined inside multimodal phenomena. The texts are represented from the effective realizations of the different option systems that allow them to be formed (written language, images, graphic designs, among others) (O’Halloran 2012). Spanish is a pluricentric languages (R. Muhr, Marley 2015 ) and this presupposes the idea of linguistic variation, thus opening a space for political, economic and social debate on the language/s that is visualized in the materiality of the manuals used and that allows us as well to make hypothesis about the position of local publishers in relation to Spanish ones, a position that is not only linguistic but also fundamentally ideological. From this panorama several questions arise, since there is a whole continent that speaks Spanish and even so is Spain the actual center of this industry, and Spanish publishers are the ones installed as hegemonic and dominant. The theoretical framework to be used will come mainly from the contributions of functional systemic linguistics, which understands that verbal language is inscribed within a social semiotics (Halliday, 1978; van Leeuwen, 2005) and, especially, from the developments of multimodal studies of the language, attending to the notions of discourse, design, production and distribution of the manuals (O’Halloran 2010, Kress, 2009).